2010
DOI: 10.1021/ie100405h
|View full text |Cite
|
Sign up to set email alerts
|

Long-Time Behavior of the Catalytic Partial Oxidation of Glycerol in an Autothermal Reactor

Abstract: We performed a long-term study of the autothermal reforming of glycerol. Liquid glycerol and water were introduced into a quartz reactor at room temperature and mixed with air in a nebulizer. The aerosol reacted to form H2, H2O, CO, and CO2 over a bed of spherical Rh−Ce/CeO2/Al2O3 particles, with minor production of C2+ species. Catalyst deactivation was exhibited by a decrease in the production of H2 and CO2 and increases in CO and temperature over 450 h. The product changes suggest reduction in the water−gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…When purification and global production costs were compared with the commercial prices of glycerol and fuel ethanol from corn and sugarcane, the purification cost of raw glycerol was lower than previously reported values due to the methanol recovery. Similarly, the use of partial oxidation and autothermal reforming have been reported in several other works with >70% H 2 yield and >80% glycerol conversion [59,65,[83][84][85][86].…”
Section: Ethanolmentioning
confidence: 55%
“…When purification and global production costs were compared with the commercial prices of glycerol and fuel ethanol from corn and sugarcane, the purification cost of raw glycerol was lower than previously reported values due to the methanol recovery. Similarly, the use of partial oxidation and autothermal reforming have been reported in several other works with >70% H 2 yield and >80% glycerol conversion [59,65,[83][84][85][86].…”
Section: Ethanolmentioning
confidence: 55%
“…In this Downloaded by [Princeton University] at 04: 47 17 September 2013 context, it is worth noting that the conditions for staying at a thermoneutral state are also heavily dependent on the ratio of steam/glycerol and the ratio of oxygen/glycerol as well as the temperatures. Moreover, the thermoneutral conditions can abate the formation of methane and carbon (101,102,103). Nevertheless, as demonstrated by the catalytic performances over Rh-Ce catalysts, the autothermal steam reforming of glycerol combined with the catalytic partial oxidation was favorable to produce syngas as the target product (103).…”
Section: Supported Pt Rh and Ru Catalystsmentioning
confidence: 96%
“…They recently employed a nebulizer injecting glycerol as small droplets into the catalytic zone with millisecond contact times 11,12 and reported that a high glycerol feed rate together with the presence of O 2 promotes oxidation, which yields sufficient heat to ignite the catalyst in autothermal mode. The ignited catalyst volatilizes and activates glycerol concurrently, allowing a design that does not require preheating.…”
Section: Introductionmentioning
confidence: 99%